STRATEGI BAURAN PEMASARAN JASA DALAM MENINGKATKAN JUMLAH JAMAAH UMRAH (Studi Kasus Pada PT. UGTMAS Tour and Travel Pasuruan) - Sifak, Mukhammad; Asnawi, H. Nur; Firmansyah, Fani (ITB AAS Indonesia Surakarta, 2024)
The tourism industry, especially in Umrah travel services, has experienced significant development in recent decades. One of the companies that plays an important role in this industry is UGTMAS Tour and Travel. As an Umrah service provider that aims to continue to increase the number of Umrah pilgrims using its services. In this context, the marketing mix becomes crucial to study and optimize in order to achieve this goal. At this time, tourism growth is very rapid, as in Umrah travel tourism, it is necessary to know, while for Umrah, 2019 (Himpuh, 2023) This study uses a qualitative approach using the case study method to examine information on the marketing mix strategy of PT UGTMAS tour and travel. Data were collected through in-depth interviews with Informants such as the President Director, Operational Director, and Marketing and Equipment Staff. In addition, Field Observations and analysis of program documents were also carried out to obtain a comprehensive picture. Data were analyzed using Cresswell's Theory, Organizing and preparing data to be analyzed, Reading and viewing all data, Coding/marking all data, Using coding as material for creating descriptions, Connecting between themes, presenting and visualizing data. 3.1. Pilgrims' Decision in Choosing UGTMAS Tour and Travel Based on the results of the survey and interviews with pilgrims, there are several main factors that are considered in choosing UGTMAS Tour and Travel as an umrah service provider, namely: a) Affordable Prices The umrah package prices offered by UGTMAS are quite competitive compared to other travel agencies, with good service quality. In addition to offering a variety of products, UGTMAS is also known for setting umrah package prices that are quite affordable compared to other umrah travel agencies, but still maintaining good service quality. This competitive pricing strategy is one of the important factors that attracts prospective pilgrims. 3.2 Internal and External Factors that Influence the Implementation of Marketing Mix Strategy. Several internal factors that influence the implementation of UGTMAS' marketing mix strategy include: a) Human Resources (Quality and Quantity of Marketing Staff) Human resources are the main asset for service companies such as UGTMAS in implementing marketing strategies. The quality and quantity of marketing staff greatly influence the success of the implementation of the marketing mix. 3.3 Implementation of Current Marketing Mix Strategy at UGTMAS Tour and Travel Currently, UGTMAS has implemented the 7P marketing mix strategy quite comprehensively, although there is still room for improvement. The right service marketing mix strategy is very important for UGTMAS Tour and Travel in attracting potential Umrah pilgrims. The company needs to consider internal factors such as human resources and marketing budget, as well as external factors such as competition and technological developments. The implementation of 7P (product, price, place, promotion, people, process, and physical evidence) consistently and sustainably can increase the number of pilgrims using UGTMAS services. However, continuous improvement is also needed to face the ever-changing market dynamics.